Membangun Generasi Berkarakter Religius: Strategi Kepala Sekolah SMP IT Bina Insani Kediri dalam Bina Pribadi Islam - Al Hulaymi, Diva Salma; Munifah, Munifah; Septiana, Nila Zaimatus (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2024)
This study examines the implementation of the Islamic Personal Development Program (BPI) at SMPIT Bina Insani Kediri City in forming students' religious character. The methodology used is a case study with narrative analysis and data collection techniques in the form of observation, in-depth interviews, and document analysis. The study results indicate that this program has succeeded in improving aspects of students' faith, worship, and morals and strengthening their social relationships in the school and community environment. The program's implementation is carried out through an integrated curriculum approach involving activities such as Qowamah, Nisaiyah, and Mabit and is supported by ongoing evaluation involving teachers and parents. The success of this program emphasizes the importance of habituating consistency and multi-party collaboration in creating a compelling educational character.